INOVASI APLIKASI SADAR LINGKUNGAN BERBASIS ANDROID (SALING BANGGA) - Suwali, Suwali; Suprapto, Suprapto; Panunggul, Victor Bintang; Sitanini, Ayu; Noviani, Faizah; Irma Azalia, Inez (ADIMA Jurnal Awatara Pengabdian Kepada Masyarakat, 2024)
Climate change and environmental degradation are pressing global issues, particularly in Indonesia. Many communities lack the information and facilities to engage in environmental conservation efforts. The "Android-based Environmental Awareness" application, or "Saling Bangga," is designed as a digital solution to enhance community awareness and participation in environmental activities. This study utilized surveys, user-centered design, and an Agile approach for app development. Implementation took place in Purbalingga District, Purbalingga Regency, involving the general public, youth, students, local government, and NGOs. The results showed a significant increase in community awareness and participation regarding environmental issues. Users reported positive behavioral changes, such as increased recycling and waste reduction. "Saling Bangga" provides an educational and interactive platform, facilitating the reporting of environmental issues and encouraging active involvement in local environmental activities. The app also successfully fostered collaboration between the community and stakeholders in addressing environmental problems. This study concludes that digital technology, particularly mobile applications, holds great potential to enhance community participation in environmental conservation.